Enhanced mineralization of aqueous Reactive Black 5 by catalytic ozonation in the presence of modified GAC. Issue 32 (8th July 2016) - He, Hongping; Wu, Deli; Lv, Yaping; Ma, Luming
Abstract: A modification of granular activated carbon (GAC) by Fe–Mn–O was proposed to improve the catalytic activity of GAC for the enhanced mineralization of aqueous RB5. The efficiency, kinetics, and possible mechanism of ozonation of aqueous RB5 catalyzed by GAC and mGAC have been investigated. mGAC exerted enhanced catalytic activity in the mineralization of aqueous RB5 and a slight promotion in decoloration. An additional 18% TOC removal efficiency was observed in the degradation of RB5 by O3 /mGAC compared with O3 /GAC under identical experimental conditions within 1 h. The pH exerted an evident impact on the degradation of RB5, with maximal mineralization achieved at pH 7. mGAC showed stable catalytic activity in the ozonation of aqueous RB5. Reaction kinetics showed that the TOC removal rate constant of RB5 degradation by O3 /mGAC was 5.4 times higher than that by O3 alone. The reaction mechanism involved the enhanced mineralization of aqueous RB5 at the catalyst–solution interface via hydroxyl radicals produced by the reaction between O3 and the surface of mGAC.